Human ectonucleotidase-expressing CD25high Th17 cells accumulate in breast cancer tumors and exert immunosuppressive functions. (2nd January 2016) - Thibaudin, Marion; Chaix, Marie; Boidot, Romain; Végran, Frédérique; Derangère, Valentin; Limagne, Emeric; Berger, Hélène; Ladoire, Sylvain; Apetoh, Lionel; Ghiringhelli, François
Abstract : Th17 cells contribute to the development of some autoimmune and allergic diseases by driving tissue inflammation. However, the function of Th17 cells during cancer progression remains controversial. Here, we show that human memory CD25 high Th17 cells suppress T cell immunity in breast cancer. Ectonucleotidase-expressing Th17 cells accumulated in breast cancer tumors and suppressed CD4 + and CD8 + T cell activation. These cells expressed both Rorγt and Foxp3 genes and secreted Th17 related cytokines. We further found that CD39 ectonucleotisase expression on tumor-infiltrating Th17 cells was driven by TGF-βand IL-6. Finally, immunohistochemical analysis of localized breast cancer revealed that high-tumor infiltration by IL-17 + cells was associated with a poor clinical outcome and impeded the favorable effect of high CD8 + infiltration. Altogether, these findings suggest that intratumoral Th17 cells compromise anticancer immune responses in breast cancer patients.